Iatrogenic Right-Sided Pneumothorax Presenting as ST-Segment Elevation: A Rare Case Report and Review of Literature - Bashar Alzghoul; Ayoub Innabi; Anusha Shanbhag; Kshitij Chatterjee; Farah Amer; Nikihil Meena (Case Reports in Critical Care)
Pneumothorax is a well-recognized complication of central venous line insertion (CVL). Rarely, pneumothorax can lead to electrocardiogram (ECG) findings mimicking ST-segment elevation myocardial infarction. We present a 63-year-old man with iatrogenic right-sided pneumothorax who developed ST-segment elevation on a 12-lead ECG suggestive of myocardial infarction. The ECG findings completely resolved after needle decompression and chest tube placement. This case points up this rare electrocardiographic finding with discussion of possible mechanisms and differential diagnosis.